(untitled) (LEGAL DIALOGICA, 2025)
This study addresses the urgency of law enforcement against election crimes conducted by the Integrated Law Enforcement Center in the context of elections in Makassar City. The research was conducted using an empirical legal method through interviews, direct observation, and document analysis to understand the operational dynamics of the involved institutions. The findings reveal that the enforcement process faces several obstacles, including limited human resources, technical difficulties in evidence collection, and political interference that can hinder the handling of cases. Nevertheless, the Integrated Law Enforcement Center has shown the ability to respond promptly to reported violations, playing a critical role in maintaining the integrity and fairness of the democratic electoral process. The coordination among the supervisory body, the police, and the prosecution office is central, yet still needs structured improvement to ensure consistency and legal certainty in handling election crimes. Enhancing the capacity of each institution’s personnel, integrating coordination systems, and applying digital technology in both monitoring and reporting processes are necessary steps to support more effective enforcement. These improvements are expected to contribute to a more transparent, accountable, and impartial electoral law enforcement mechanism in future elections. Abstrak: Penelitian ini membahas urgensi efektivitas kerja Sentra Penegakan Hukum Terpadu dalam proses penegakan hukum terhadap tindak pidana pemilu, khususnya dalam konteks pelaksanaan pemilu di Kota Makassar. Penelitian ini menggunakan metode empiris dengan pendekatan wawancara dan observasi langsung untuk memperoleh data lapangan yang dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa pelaksanaan tugas Gakkumdu dalam menangani tindak pidana pemilu masih menghadapi berbagai hambatan, seperti keterbatasan sumber daya manusia, kendala teknis dalam proses pembuktian, serta adanya potensi intervensi dari kepentingan politik. Meskipun demikian, Gakkumdu mampu merespons laporan secara cepat dan menunjukkan peranan penting dalam menjaga integritas demokrasi melalui penanganan pelanggaran pemilu. Koordinasi antara lembaga yang tergabung dalam Gakkumdu dinilai telah berjalan, namun masih perlu diperkuat melalui sistem yang lebih terstruktur dan terpadu. Temuan ini menegaskan perlunya peningkatan kapasitas kelembagaan, penyempurnaan mekanisme koordinasi antarlembaga, serta pemanfaatan teknologi informasi untuk menunjang efektivitas pengawasan dan penegakan hukum. Penelitian ini merekomendasikan penguatan kapasitas teknis dan kelembagaan Gakkumdu serta pengembangan sistem digital pelaporan sebagai strategi untuk meningkatkan kualitas penegakan hukum terhadap tindak pidana pemilu pada masa mendatang.